2016
DOI: 10.1016/j.minpro.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of hydrochloric acid leaching of niobium from TiO2 residues

Abstract: Production of TiO2 generates waste containing significant quantities of valuable metals which if recovered, could have a positive impact on the economics of TiO2 production and waste management. In this investigation, the kinetics of HCl leaching of niobium from TiO2 residues are studied. The complex mineralisation of niobium in its primary ores makes economic recovery very difficult, often demanding the use of chlorination, carbochlorination or fusion with alkali fluxes for breakdown of its mineral concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…Both metals are also similar in terms of chemical and physical properties which renders their separation and purification difficult (Ayanda and Adekola, 2011). However, their abundance in the earth's crust is quite low, Ta being found around 2 ppm (Bose and Gupta, 2002;Soedarsono et al, 2018;Yang et al, 2018) and Nbaround 24 ppm (Makanyire et al, 2016;Allain et al, 2019). This limited availability is driving the need to valorise secondary raw materials containing Ta and Nb, among them tin slags, but also metallic scraps and by-products.…”
Section: Introductionmentioning
confidence: 99%
“…Both metals are also similar in terms of chemical and physical properties which renders their separation and purification difficult (Ayanda and Adekola, 2011). However, their abundance in the earth's crust is quite low, Ta being found around 2 ppm (Bose and Gupta, 2002;Soedarsono et al, 2018;Yang et al, 2018) and Nbaround 24 ppm (Makanyire et al, 2016;Allain et al, 2019). This limited availability is driving the need to valorise secondary raw materials containing Ta and Nb, among them tin slags, but also metallic scraps and by-products.…”
Section: Introductionmentioning
confidence: 99%
“…This type of reaction mechanism does not occur in a REE solution since the REEs exist mostly as a compound. Niobium leaching from titanium oxide residues did not show any effect from the S/L ratio on leaching recovery [21]. However, Li et al (2013) reported on a rare earth concentrate leaching study that found the S/L ratio to have a negative effect on the leaching of a rare earth concentrate when the ratio was higher than 100 g/L [23].…”
Section: Solid-to-liquid Ratio Effectmentioning
confidence: 93%
“…Stirring speed affects the thickness of the film layer surrounding a solid particle suspended in the lixiviate solution. A high stirring speed creates an enhanced shear rate in solution which reduces the film layer thickness thereby increasing the mass transfer rate through the film diffusion layer [21]. The effect of stirring speed was evaluated at 300 rpm, 530 rpm, 760 rpm, and 900 rpm as shown in Figure 6.…”
Section: Stirring Speed Effectmentioning
confidence: 99%
“…Alternative non-fluoride based lixiviants, including H 2 SO 4 and HCl have also been investigated for processing Ta and Nb containing ores [8][9][10][11]. However, while some of them demonstrate reasonable leaching yields, others are witnessing low recoveries and metal yields when compared to the HF process.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the majority of the studies being done [5][6][7] are reporting to be able to recover more than 90% of Ta and Nb from tantalite (Fe,Mn)O(Ta,Nb)2O5 or columbite (Fe,Mn)O(Nb,Ta)2O5, which justifies the wider industrial-scale use of hydrofluoric acid for Ta and Nb leaching. Alternative non-fluoride based lixiviants, including H2SO4 and HCl have also been investigated for processing Ta and Nb containing ores [8][9][10][11]. However, while some of them demonstrate reasonable leaching yields, others are witnessing low recoveries and metal yields when compared to the HF process.…”
Section: Introductionmentioning
confidence: 99%